Narrowing the policy gap: lessons from years 2 and 3 of the British Columbia influenza prevention policy - Antonia M. Di Castri; Donna M. Halperin; Charmaine M. McPherson; Alexandra Nunn; Haley Farrar-Muir; Jeffrey C. Kwong; Bonnie Henry (Human Vaccines & Immunotherapeutics, 2020)
Influenza can be potentially fatal to vulnerable populations, particularly those in the hospital. Canada’s National Advisory Committee on Immunization recommends that health-care workers (HCW) be immunized against influenza partly to avoid infecting high-risk populations. However, influenza immunization rates among HCW remain suboptimal. In 2012, health authorities across British Columbia (B.C.) implemented a province-wide influenza prevention policy requiring HCW to either be immunized or wear a mask when in patient-care areas during the influenza season. This paper describes the second of two studies focused on what was learned from years 2 and 3 of the policy. A case study approach was used to examine this policy implementation event. Qualitative data were collected through key documents and key informant interviews with members of leadership teams responsible for policy implementation. Framework analysis and Prior’s approach were used to analyze data from interviews and documents, respectively. Policy implementation varied by geographic region and gaps persist in immunization tracking and discipline for noncompliance. Debate regarding the scientific evidence used to support the policy fuels resistance from particular groups. Despite these challenges, findings suggest that the policy has been habituated, largely due to consistent policy objectives. This study emphasizes the importance of ongoing inter-professional and cross-sectoral program evaluation. While adherence may be routine for many, implementation processes must continue to respond to contextual issues to narrow the gap in policy implementation and to continue to engage stakeholders to ensure compliance.